A method for preparing a COF nanofiltration membrane by using acid regulation
Patent Information
- Application Number
- CN202410400462.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-03
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-04-03
AI Technical Summary
然而现有的水处理技术代价昂贵,迫切需要研究出低成本、节能和环保的新方法来实现水净化
[0019]本发明利用酸浓度调控席夫碱反应反应速率制备纳滤膜,以形成有序的传输通道,有效的提高了膜的传质速率,同时保持较高的分离性能;该类方法操作简单且绿色环保,具有工业推广潜力。利用该技术制备的TpPa纳滤膜的纯水通量为139.3L·m-2·h-1·bar-1,对伊文斯蓝(EB)、刚果红(CR)、甲基蓝(MB)的截留率分别为99.6%、98.6%、90.0%。制备过程简单,重复性好,在有机物废水脱盐领域有很大的潜在应用前景。
Smart Images

Figure HDA0004775466060000011 
Figure HDA0004775466060000012 
Figure HDA0004775466060000021
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing high-flux COF nanofiltration membranes using an acid-controlled method, belonging to the field of membrane separation. Background Technology
[0002] Water scarcity has become a global crisis. Dye wastewater is typically characterized by high color intensity and biotoxicity, while the inorganic salts in dyes can disrupt the osmotic pressure of aquatic organisms, causing dehydration and death. To mitigate its harm to the ecological environment and human health, graded treatment of dyes and salts is essential. However, existing water treatment technologies are expensive, necessitating the research and development of new, low-cost, energy-efficient, and environmentally friendly methods for water purification.
[0003] Membrane technology has attracted much attention due to its advantages such as no phase change, low energy consumption, short operation time, good safety, and environmental friendliness. Among them, nanofiltration (NF) membranes are a pressure-driven membrane separation process with a molecular weight cutoff of 200-1000 Da and a pore size of approximately 0.5-2.0 nm, which can effectively perform fractional processing of dyes / salts. COF membranes, in particular, are characterized by high porosity, regular pore structure, and good stability. Summary of the Invention
[0004] The purpose of this invention is to regulate the formation of COFs nanofiltration membranes by varying acid concentrations, thereby constructing a regular crystal structure, forming ordered pores, shortening the mass transfer path, and improving the mass transfer rate. COFs nanofiltration membranes prepared using this method exhibit excellent separation performance and extremely high flux in the field of nanofiltration separation.
[0005] A method for preparing a high-flux COF nanofiltration membrane includes the following steps:
[0006] Step 1: Immerse the pretreated base membrane in an aqueous solution containing p-phenylenediamine (Pa) protic acid, and under negative pressure, allow the solution to fill the porous base membrane.
[0007] Step 2: Remove the base membrane surface solution from Step 1, pour a hexane solution of 1,3,5-trialdehyde phloroglucinol (Tp) to allow it to undergo interfacial polymerization at the phase interface to form a separation layer, dry it, activate it with methanol, and store it in deionized water to obtain the high-flux COF nanofiltration membrane.
[0008] The Schiff base reaction typically involves three steps: initial nucleophilic reaction, water molecule desorption, and Schiff base formation. In this reaction, the acid usually acts as a catalyst, accelerating the nucleophilic reaction. When the acid concentration is ≤40 wt%, H... +It promotes the protonation of -C=O, accelerating the Schiff base reaction rate. 1,3,5-Trialdehyde phloroglucinol (Tp) reacts rapidly with p-phenylenediamine (Pa), ultimately forming a disordered stacked structure, resulting in lower performance. However, when the acid concentration is ≥50wt%, H… + Occupying the lone pair of electrons in -NH2 interferes with the reaction between the nucleophile and the active carbonyl group, thereby reducing the nucleophilic reaction rate and hindering the formation of Schiff bases. Therefore, the reaction rate between 1,3,5-trialdehyde phloroglucinol (Tp) and p-phenylenediamine (Pa) is reduced at the interface. Their microstructures are arranged in an ordered manner, forming an ordered pore structure, shortening the mass transfer path and achieving precise sieving.
[0009] In one embodiment, the concentration of protic acid is 50-60 wt%.
[0010] In one embodiment, the protic acid includes acetic acid or p-toluenesulfonic acid.
[0011] In one embodiment, the negative pressure state is maintained for 20 to 40 minutes in step 1; the interfacial polymerization reaction time in step 2 should be 5 to 30 minutes.
[0012] In one embodiment, the concentration of p-phenylenediamine in step 1 is 2.00 wt%; the concentration of protic acid is 50 wt%.
[0013] In one embodiment, the concentration of 1,3,5-trialdehyde phloroglucinol in step 2 is 0.02 wt%.
[0014] In one embodiment, the pretreatment in step 1 is to remove organic matter, inorganic matter and microorganisms from its surface.
[0015] In one embodiment, the pretreatment method is to soak in anhydrous ethanol for 1-3 hours, then rinse with deionized water and store.
[0016] In one embodiment, the base film material includes polyacrylonitrile.
[0017] In one embodiment, the pore size of the base film material is 0.1µm to 0.005µm.
[0018] Beneficial effects
[0019] This invention utilizes acid concentration to regulate the Schiff base reaction rate to prepare nanofiltration membranes, thereby forming ordered transport channels and effectively improving the membrane's mass transfer rate while maintaining high separation performance. This method is simple to operate, environmentally friendly, and has potential for industrial application. The TpPa nanofiltration membrane prepared using this technology has a pure water flux of 139.3 L·m⁻¹. -2 ·h -1 ·bar -1The retention rates for Evans Blue (EB), Congo Red (CR), and Methylene Blue (MB) were 99.6%, 98.6%, and 90.0%, respectively. The preparation process is simple and reproducible, and it has great potential application prospects in the field of organic wastewater desalination. Attached Figure Description
[0020] Figure 1 The images show the XRD patterns of the films prepared at different reaction times (TpPa) in Examples 1-5.
[0021] Figure 2 The graphs show the performance of membranes with different acid concentrations (TpPa) prepared in Examples 1-5.
[0022] Figure 3 The images show the XRD patterns of the TpPa films prepared in Examples 6-12 at different reaction times.
[0023] Figure 4 The graphs show the performance of membranes with different acid concentrations (TpPa) prepared in Examples 6-12. Detailed Implementation
[0024] The present invention will be described in detail below with reference to specific embodiments, but the present invention is not limited to the following embodiments.
[0025] Example 1: Preparation of TpPa5
[0026] (1) Pre-treat the PAN porous base membrane to remove organic matter, inorganic matter and microorganisms from its surface;
[0027] (2) Immerse the PAN base film from step (1) in a 2.00wt% Pa-H2O solution (containing 50wt% HAc) and maintain a negative pressure for 30 minutes to ensure complete immersion.
[0028] (3) Remove the liquid from the surface of the PAN base film in step (2), and then slowly pour 0.02wt% Tp-Hexane solution onto the surface to carry out interfacial polymerization reaction for 5 min, and then dry at 60℃ for 5 min to form TpPa5 film;
[0029] (4) Activate the TpPa5 membrane from step (3) with methanol three times, and then store it with deionized water;
[0030] (5) The TpPa5 membrane was treated with 0.1 g·L⁻¹ water. -1 The aqueous solutions of Evans Blue (EB), Congo Red (CR), and Methyl Blue (MB) were tested, and the pure water flux was 305 L·m⁻¹ at an operating pressure of 0.2 MPa. -2 ·h -1 ·bar -1 The retention rates were 88%, 87%, and 41%, respectively.
[0031] Example 2: Preparation of TpPa9
[0032] (1) Pre-treat the PAN porous base membrane to remove organic matter, inorganic matter and microorganisms from its surface;
[0033] (2) Immerse the PAN base film from step (1) in a 2.00wt% Pa-H2O solution (containing 50wt% HAc) and maintain a negative pressure for 30 minutes to ensure complete immersion.
[0034] (3) Remove the liquid from the surface of the PAN base film in step (2), and then slowly pour 0.02wt% Tp-Hexane solution onto the surface to carry out interfacial polymerization reaction for 9 min, and then dry at 60℃ for 5 min to form TpPa9 film.
[0035] (4) Activate the TpPa9 membrane from step (3) with methanol three times, and then store it with deionized water;
[0036] (5) The TpPa9 membrane was treated with 0.1 g·L⁻¹ water. -1 The aqueous solutions of Evans Blue (EB), Congo Red (CR), and Methylene Blue (MB) were tested, and the pure water flux was 212 L·m⁻¹ at an operating pressure of 0.2 MPa. -2 ·h -1 ·bar -1 The retention rates were 98%, 96%, and 79%, respectively.
[0037] Example 3: Preparation of TpPa10
[0038] (1) Pre-treat the PAN porous base membrane to remove organic matter, inorganic matter and microorganisms from its surface;
[0039] (2) Immerse the PAN base film from step (1) in a 2.00wt% Pa-H2O solution (containing 50wt% HAc) and maintain a negative pressure for 30 minutes to ensure complete immersion.
[0040] (3) Remove the liquid from the surface of the PAN base film in step (2), and then slowly pour 0.02wt% Tp-Hexane solution onto the surface to carry out interfacial polymerization reaction for 10 min, and then dry at 60℃ for 5 min to form TpPa10 film.
[0041] (4) Activate the TpPa10 membrane from step (3) three times with methanol, and then store it with deionized water;
[0042] (5) The TpPa10 membrane was treated with 0.1 g·L⁻¹ water. -1 The aqueous solutions of Evans Blue (EB), Congo Red (CR), and Methylene Blue (MB) were tested, and the pure water flux was 139 L·m⁻¹ at an operating pressure of 0.2 MPa. -2 ·h-1 ·bar -1 The retention rates were 99%, 99%, and 90%, respectively.
[0043] Example 4: Preparation of TpPa12
[0044] (1) Pre-treat the PAN porous base membrane to remove organic matter, inorganic matter and microorganisms from its surface;
[0045] (2) Immerse the PAN base film from step (1) in a 2.00wt% Pa-H2O solution (containing 50wt% HAc) and maintain a negative pressure for 30 minutes to ensure complete immersion.
[0046] (3) Remove the liquid from the surface of the PAN base film in step (2), and then slowly pour 0.02wt% Tp-Hexane solution onto the surface to carry out interfacial polymerization reaction for 12 min, and then dry at 60℃ for 5 min to form TpPa12 film.
[0047] (4) Activate the TpPa12 membrane from step (3) three times with methanol, and then store it with deionized water;
[0048] (5) The TpPa12 membrane was treated with 0.1 g·L⁻¹ water. -1 The aqueous solutions of Evans Blue (EB), Congo Red (CR), and Methylene Blue (MB) were tested, and the pure water flux was 112 L·m⁻¹ at an operating pressure of 0.2 MPa. -2 ·h -1 ·bar -1 The retention rates were 99%, 99%, and 94%, respectively.
[0049] Example 5: Preparation of TpPa15, TpPa20, and TpPa30
[0050] The preparation methods of TpPa15, TpPa20, and TpPa30 are the same as in Example 1, except that the interfacial polymerization reaction time in step (3) is adjusted to 15 min, 20 min, and 30 min, respectively.
[0051] Depend on Figure 1 and Figure 2 The performance and XRD analysis of TpPa membranes prepared at different reaction times were presented. When the reaction time was greater than 10 min, the TpPa membrane began to show obvious crystallization peaks, indicating the formation of an ordered pore structure. However, with the extension of reaction time, the thickness of the separation layer gradually increased, the mass transfer path lengthened, and the flux gradually decreased.
[0052] Example 6: Preparation of TpPa10-5
[0053] (1) Pre-treat the PAN porous base membrane to remove organic matter, inorganic matter and microorganisms from its surface;
[0054] (2) Immerse the PAN base film from step (1) in a 2.00wt% Pa-H2O solution (containing 5wt% HAc) and maintain a negative pressure for 30 minutes to ensure complete immersion;
[0055] (3) Remove the liquid from the surface of the PAN base film in step (2), and then slowly pour 0.02wt% Tp-Hexane solution onto the surface to carry out interfacial polymerization reaction for 10 min, and then dry at 60℃ for 5 min to form TpPa10-5 film.
[0056] (4) Activate the TpPa10-5 membrane from step (3) three times with methanol, and then store it with deionized water;
[0057] (5) The TpPa10-5 membrane was treated with 0.1 g·L⁻¹ water. -1 The aqueous solutions of Evans Blue (EB), Congo Red (CR), and Methylene Blue (MB) were tested, and the pure water flux was 3.4 L·m⁻¹ at an operating pressure of 0.2 MPa. -2 ·h -1 ·bar -1 The retention rates were 99%, 99%, and 99%, respectively.
[0058] Example 7: Preparation of TpPa10-10
[0059] (1) Pre-treat the PAN porous base membrane to remove organic matter, inorganic matter and microorganisms from its surface;
[0060] (2) Immerse the PAN base film from step (1) in a 2.00wt% Pa-H2O solution (containing 10wt% HAc) and maintain a negative pressure for 30 minutes to ensure complete immersion.
[0061] (3) Remove the liquid from the surface of the PAN base film in step (2), and then slowly pour 0.02wt% Tp-Hexane solution onto the surface to carry out interfacial polymerization reaction for 10 min, and then dry at 60℃ for 5 min to form TpPa10-10 film.
[0062] (4) Activate the TpPa10-10 membrane from step (3) three times with methanol, and then store it with deionized water;
[0063] (5) The TpPa10-10 membrane was treated with 0.1 g·L⁻¹ water. -1 The aqueous solutions of Evans Blue (EB), Congo Red (CR), and Methylene Blue (MB) were tested, and the pure water flux was 3.1 L·m⁻¹ at an operating pressure of 0.2 MPa. -2 ·h -1 ·bar -1 The retention rates were 99%, 99%, and 99%, respectively.
[0064] Example 8: Preparation of TpPa10-20
[0065] (1) Pre-treat the PAN porous base membrane to remove organic matter, inorganic matter and microorganisms from its surface;
[0066] (2) Immerse the PAN base film from step (1) in a 2.00wt% Pa-H2O solution (containing 20wt% HAc) and maintain a negative pressure for 30 minutes to ensure complete immersion;
[0067] (3) Remove the liquid from the surface of the PAN base film in step (2), and then slowly pour 0.02wt% Tp-Hexane solution onto the surface to carry out interfacial polymerization reaction for 10 min, and then dry at 60℃ for 5 min to form TpPa10-20 film.
[0068] (4) Activate the TpPa10-20 membrane from step (3) three times with methanol, and then store it with deionized water;
[0069] (5) The TpPa10-20 membrane was treated with 0.1 g·L⁻¹ water. -1 The aqueous solutions of Evans Blue (EB), Congo Red (CR), and Methylene Blue (MB) were tested, and the pure water flux was 3.1 L·m⁻¹ at an operating pressure of 0.2 MPa. -2 ·h -1 ·bar -1 The retention rates were 99%, 99%, and 99%, respectively.
[0070] Example 9: Preparation of TpPa10-30
[0071] (1) Pre-treat the PAN porous base membrane to remove organic matter, inorganic matter and microorganisms from its surface;
[0072] (2) Immerse the PAN base film from step (1) in a 2.00wt% Pa-H2O solution (containing 30wt% HAc) and maintain a negative pressure for 30 minutes to ensure complete immersion;
[0073] (3) Remove the liquid from the surface of the PAN base film in step (2), and then slowly pour 0.02wt% Tp-Hexane solution onto the surface to carry out interfacial polymerization reaction for 10 min, and then dry at 60℃ for 5 min to form TpPa10-30 film.
[0074] (4) Activate the TpPa10-30 membrane from step (3) three times with methanol, and then store it with deionized water;
[0075] (5) The TpPa10-30 membrane was treated with 0.1 g·L⁻¹ water. -1The aqueous solutions of Evans Blue (EB), Congo Red (CR), and Methylene Blue (MB) were tested, and the pure water flux was 3.3 L·m⁻¹ at an operating pressure of 0.2 MPa. -2 ·h -1 ·bar -1 The retention rates were 99%, 99%, and 99%, respectively.
[0076] Example 10: Preparation of TpPa10-40
[0077] (1) Pre-treat the PAN porous base membrane to remove organic matter, inorganic matter and microorganisms from its surface;
[0078] (2) Immerse the PAN base film from step (1) in a 2.00wt% Pa-H2O solution (containing 40wt% HAc) and maintain a negative pressure for 30 minutes to ensure complete immersion.
[0079] (3) Remove the liquid from the surface of the PAN base film in step (2), and then slowly pour 0.02wt% Tp-Hexane solution onto the surface to carry out interfacial polymerization reaction for 10 min, and then dry at 60℃ for 5 min to form TpPa10-40 film.
[0080] (4) Activate the TpPa10-40 membrane from step (3) three times with methanol, and then store it with deionized water;
[0081] (5) The TpPa10-40 membrane was treated with 0.1 g·L⁻¹ water. -1 The aqueous solutions of Evans Blue (EB), Congo Red (CR), and Methylene Blue (MB) were tested, and the pure water flux was 5.4 L·m⁻¹ at an operating pressure of 0.2 MPa. -2 ·h -1 ·bar -1 The retention rates were 99%, 99%, and 99%, respectively.
[0082] Example 11 Preparation of TpPa10-50
[0083] (1) Pre-treat the PAN porous base membrane to remove organic matter, inorganic matter and microorganisms from its surface;
[0084] (2) Immerse the PAN base film from step (1) in a 2.00wt% Pa-H2O solution (containing 50wt% HAc) and maintain a negative pressure for 30 minutes to ensure complete immersion.
[0085] (3) Remove the liquid from the surface of the PAN base film in step (2), and then slowly pour 0.02wt% Tp-Hexane solution onto the surface to carry out interfacial polymerization reaction for 10 min, and then dry at 60℃ for 5 min to form TpPa10-50 film.
[0086] (4) Activate the TpPa10-50 membrane from step (3) three times with methanol, and then store it with deionized water;
[0087] (5) The TpPa10-50 membrane was treated with 0.1 g·L⁻¹ water. -1 The aqueous solutions of Evans Blue (EB), Congo Red (CR), and Methylene Blue (MB) were tested, and the pure water flux was 139 L·m⁻¹ at an operating pressure of 0.2 MPa. -2 ·h -1 ·bar -1 The retention rates were 99%, 99%, and 90%, respectively.
[0088] Example 12 Preparation of TpPa10-60
[0089] 1) Pre-treat the PAN porous base membrane to remove organic matter, inorganic matter and microorganisms from its surface;
[0090] (2) Immerse the PAN base film from step (1) in a 2.00wt% Pa-H2O solution (containing 60wt% HAc) and maintain a negative pressure for 30 minutes to ensure complete immersion.
[0091] (3) Remove the liquid from the surface of the PAN base film in step (2), and then slowly pour 0.02wt% Tp-Hexane solution onto the surface to carry out interfacial polymerization reaction for 10 min, and then dry at 60℃ for 5 min to form TpPa10-60 film.
[0092] (4) Activate the TpPa10-60 membrane from step (3) three times with methanol, and then store it with deionized water;
[0093] (5) The TpPa10-60 membrane was treated with 0.1 g·L⁻¹ water. -1 The aqueous solutions of Evans Blue (EB), Congo Red (CR), and Methyl Blue (MB) were tested, and the pure water flux was 125 L·m⁻¹ at an operating pressure of 0.2 MPa. -2 ·h -1 ·bar -1 The retention rates were 99%, 97%, and 83%, respectively.
[0094] Depend on Figure 3 and Figure 4 The performance and XRD analysis of TpPa membranes prepared with different acid concentrations were studied. When the acid concentration was ≤40wt%, H + Promoting the protonation of -C=O accelerates the Schiff base reaction rate, forming a disordered stacked TpPa separation layer, but its pure water flux is too low; when the acid concentration is ≥50wt%, H +By occupying the lone pair of electrons in -NH2, the reaction between the nucleophile and the active carbonyl group is interfered with, thereby reducing the reaction rate, forming an ordered pore structure, shortening the mass transfer path, and achieving precise sieving.
Claims
1. A method for preparing COF nanofiltration membranes using acid regulation, characterized in that, A highly crystalline nanofiltration membrane is prepared by acid-controlled Schiff base reaction. The method includes the following steps: Step 1: Immerse the pretreated base membrane in an aqueous solution containing p-phenylenediamine and protic acid, maintaining a negative pressure to ensure the solution fills the porous base membrane; the concentration of p-phenylenediamine is 1.5wt%~3.00wt%; the concentration of protic acid is 50wt%~60wt%. Step 2: Remove the solution from the base membrane surface in Step 1, pour in a 0.02wt% hexane solution of 1,3,5-trialdehyde phloroglucinol, and allow it to undergo interfacial polymerization at the phase interface to form a separation layer. After drying, activate it with methanol and store it in deionized water to obtain the COF nanofiltration membrane. The interfacial polymerization reaction time should be 5 min to 30 min.
2. The method for preparing COF nanofiltration membranes using acid regulation according to claim 1, characterized in that, The protic acid includes acetic acid or p-toluenesulfonic acid.
3. The method for preparing COF nanofiltration membranes using acid regulation according to claim 1, characterized in that, In step 1, maintain a negative pressure state for 20-40 minutes; in step 2, the interfacial polymerization reaction time should be 10 minutes.
4. A method for preparing COF nanofiltration membranes using acid regulation according to claim 1 or 2, characterized in that, In step 1, the concentration of protic acid is 50 wt%.
5. The method for preparing COF nanofiltration membranes using acid regulation according to claim 1, characterized in that, The pretreatment in step 1 is to remove organic matter, inorganic matter and microorganisms from its surface.
6. A method for preparing COF nanofiltration membranes using acid regulation according to claim 1 or 5, characterized in that, The pretreatment method is to soak in anhydrous ethanol for 1-3 hours, then rinse with deionized water and store.
7. The method for preparing COF nanofiltration membranes using acid regulation according to claim 1, characterized in that, The base film material includes polyacrylonitrile.
8. A method for preparing a COF nanofiltration membrane using acid regulation according to claim 1 or 7, characterized in that, The pore size of the base film material is 0.1um to 0.005um.
Citation Information
Patent Citations
High-flux covalent organic skeleton composite membrane and preparation method thereof
CN107983173A
Covalent organic framework polycrystalline dense film as well as preparation method and application thereof
CN116272400A